Speech Activity as a Component of the Psycholinguistics Object - Kalmykova, Larysa (East European Journal of Psycholinguistics, 2015)
The article deals with the problem of formation in psychology and psycholinguistics of the phenomenon of speech activity, dynamic changes in its definition and specification. The results of comparative analysis of psycholinguistics and its categorical apparatus development in foreign and Eastern European (domestic) science has been given. Much attention in this article is paid to theoretical sources of speech activity, which later evolved into psycholinguistics, where speech activity as one of its research object was singled out. Speech activity and language are viewed as components involved in formation and operation of mental reflection, as well as in mediating of human activity by this reflection;. Among other items psycholinguistics traditionally focuses on are individual emotional and motivational components (needs, motives, goals), ctivity, correspondence of the object of activity to its motive, availability of product and result of this activity, planning, structuring, aiming, etc. Speech activity is treated as an independent activity with a specific speech motive, in particular, sense formulation and sense formation. References Vygotsky, L. (2000). Mysl i Slovo [Thought and Word]. Psychology. 462–512. Zimnyaya, I. (2001). Lingvopsihologiya Rechevoy Deyatelnosti [Linguopsychology of Speech Activity] Moscow: MODEK. Kalmykova, L. (2010). Rozvytok Movlennyevoyi Diyalnosti Ditey Doshkilnoho Viku [Speech Development of Preschool Children]. Pereyaslav-Khmelnytskyi: SKD. Kalmykova, L. (2010). Psykhologiya rozvytku movlennyevoyi diyalnosti ditej doshkil`nogo viku [Psychology of preschoolers’ development of speech]. Unpublished Doctoral dissertation. Kyiv. Leontyev, A. (1969). Psikholingvisticheskie Edinitsy i Porozhdenie Rechevogo Vyskazyvaniya [Psycholinguistic Units and Production of Speech Utterance]. Moscow: Nauka. Leontyev, A. (1969). Yazyk, Rech, Rechevaya Deyatelnost [Language, Speech, Speech Activity]. Moscow: Prosveshchenie. Leontyev, A. (1990). Psikholingvistika [Psycholinguistics]. Linguistic Encyclopedic Dictionary. Moscow: Sovetskaya Entsiklopediya, 404–405. Leontyev, A. (1990). L. S. Vygotsky [L. S. Vygotsky]. Moscow: Prosveshchenie. Leontyev, A. (1997). Psikhologiya Obshcheniya [Psychology of Communication]. Moscow: Smysl. Leontyev, A. (2003). Osnovy Psikholingvistiki [Fundamentals of Psycholinguistics]. Moscow: Smysl; S.-Petersburg: Lan. Leontyev, A. (1974). Obshchee ponyatie o deyatelnosti [General notion on activity]. Osnovy Teorii Rechevoy Deyatelnosti, 5–20. Leontyev, A. (1974). Deyatelnost. Soznanie. Lichnost [Activities. Consciousness. Personality]. Moscow: Izdatelstvovo Politicheskie materialy. Psikhologiya: Slovar (1990) [Psychology: dictionary]. V. A. Petrovsky, M. G. Yaroshevsky, Eds. Moscow: Politizdat. Rubinshteyn, S. (2000). Osnovy obshchey psikhologii [Fundamentals of general psychology]. S.-Petersburg: Piter. Rumyantseva, I. (2004). Psikhologiya rechi i lingvopedagogicheskaya psikhologiya [Psychology of speech and ligvopedagogical psychology]. Moscow: PER SE; Logos.